Suporte no trabalho, vínculos organizacionais e desenvolvimento de competências profissionais: modelo integrado de estudo com jovens trabalhadores - Michelle de Souza Rocha (2021)
This study aims to analyze how the perception of support at work (organizational and social), organizational bonds (commitment, entrenchment and consent) and the professional skills of young workers allocated in a federal public company are related. For this, a descriptive and explanatory quantitative research was carried out, using an electronic questionnaire. The choice of the public is justified because it represents a group with peculiar characteristics, due to the stage of its development and because its insertion is one of the great challenges of employment policy today. It is also a more vulnerable public, which faces greater difficulties in entering the labor market and tends to find more precarious occupations, further aggravated by the low level of education and the fragility of the educational background of a large part of the population. Data from 2034 valid questionnaires were statistically treated, with all scales revalidated through exploratory factor analysis, descriptive data presented, and causality relationships tested through the structural equation modeling technique (SEM), which allowed confirming 10 of the 13 proposed hypotheses. These results allow us to confirm the thesis argument proposed in the introduction of this work, namely, "the perception of support at work (formed by organizational and social supports) fosters commitment and consent, and discourages entrenchment, having direct effects on training skills of young workers”. Finally, it is possible to highlight the following contributions of the present work: (1) elaboration of the validated theoretical model, which comprised three groups of constructs in the field of organizational behavior (support at work, organizational bonds and competences); (2) discussion and validation of the relationships between the researched constructs, some of which had not been discussed and validated in the literature before, establishing a precedent for future studies; (3) evidence of validity of the scales used for the young audience; (4) discussion about the uniqueness of Entrenchment for the studied public; (5) revalidation of the professional skills scale for young workers; (6) scope of the study, with the participation of young people from all parts of the country, which allowed for greater robustness in the findings and its applicability to the studied public; (7) representation of young workers as an academic interest group, however, still little explored. Thus, the present study contributes to the knowledge of the behavior of this public at work, as well as presenting, as its main managerial implication, the potential to guide the actions of organizations in order to develop learning programs that really contribute to the professional development of these young people, with a view to future insertions in the labor market. Research limitations and suggestions for future investigations close the study presented.